BOLD fMRI effects of transcutaneous vagus nerve stimulation in patients with chronic tinnitus - Yakunina, Natalia; Kim, Sam Soo; Nam, Eui-Cheol (PloS one, 2018)
Vagus nerve stimulation (VNS) is a neuromodulation method used for treatment of epilepsy and depression. Transcutaneous VNS (tVNS) has been gaining popularity as a noninvasive alternative to VNS. Previous tVNS neuroimaging studies revealed brain (de)activation patterns that involved multiple areas implicated in tinnitus generation and perception. In this study, functional magnetic resonance imaging (fMRI) was used to explore the effects of tVNS on brain activity in patients with tinnitus. Thirty-six patients with chronic tinnitus received tVNS to the inner tragus, cymba conchae, and earlobe (sham stimulation). The locus coeruleus and nucleus of the solitary tract in the brainstem were activated in response to stimulation of both locations compared with the sham stimulation. The cochlear nuclei were also activated, which was not observed in healthy subjects with normal hearing. Multiple auditory and limbic structures, as well as other brain areas associated with generation and perception of tinnitus, were deactivated by tVNS, particularly the parahippocampal gyrus, which was recently speculated to cause tinnitus in hearing-impaired patients. tVNS via the inner tragus or cymba conchae suppressed neural activity in the auditory, limbic, and other tinnitus-related non-auditory areas through auditory and vagal ascending pathways in tinnitus patients. The results from this study are discussed in the context of several existing models of tinnitus. They indicate that the mechanism of action of tVNS might be involved in multiple brain areas responsible for the generation of tinnitus, tinnitus-related emotional annoyance, and their mutual reinforcement.